2020
DOI: 10.3389/fimmu.2020.574997
|View full text |Cite
|
Sign up to set email alerts
|

Th17-Immune Response in Patients With Membranous Nephropathy Is Associated With Thrombosis and Relapses

Abstract: Membranous nephropathy (MN) is a rare autoimmune kidney disease. Most autoimmune diseases are associated with a pro-inflammatory Th17-immune response, but little is known about immune dysregulation in MN. In China, MN was associated with exposure to fine air particulate matter (PM2.5) that could act as a danger signal and redirect immune response toward the Th2 or Th17 pathway. We aimed to analyze the cytokine profile of MN patients and to study the possible environmental factors involved in this immune reorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 51 publications
1
39
2
1
Order By: Relevance
“…Treg frequencies increased after treatment with rituximab, indicating restoration of immune balance. In line with these results, MN patients were recently identified to have higher Th17 and Th2 cytokines (IL-17A, IL-6, and IL-4) and lower Th1 and Treg cytokines (interferon-γ and IL-10), showing a cytokine dysbalance in MN patients (Cremoni et al 2020). Interestingly, patients with the highest Th17 signature lived in areas with a higher burden of fine particulate matter, suggesting a connection between air pollution, immune dysregulation and incidence of MN.…”
Section: Disease Initiationsupporting
confidence: 61%
“…Treg frequencies increased after treatment with rituximab, indicating restoration of immune balance. In line with these results, MN patients were recently identified to have higher Th17 and Th2 cytokines (IL-17A, IL-6, and IL-4) and lower Th1 and Treg cytokines (interferon-γ and IL-10), showing a cytokine dysbalance in MN patients (Cremoni et al 2020). Interestingly, patients with the highest Th17 signature lived in areas with a higher burden of fine particulate matter, suggesting a connection between air pollution, immune dysregulation and incidence of MN.…”
Section: Disease Initiationsupporting
confidence: 61%
“…All these cells would actively respond to IL6 ( Su et al, 2017 ). Moreover, plasma and urinary IL6 concentrations correlated with proteinuria in acute Hantavirus-induced nephritis ( Mäkelä et al, 2004 ) and increased IL6 plasma levels and a TH17 profile have already been described in glomerular diseases such as membranous nephropathy ( Cremoni et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even if a case of collapsing glomerulopathy has been reported in COVID-19 ( Gaillard et al, 2020 ), acute tubular necrosis (ATN) with interstitial component probably remains the main cause of kidney injury. Other factors may contribute to kidney involvement: systemic inflammation and cytokine storm ( Burton and Harris, 1996 ; Coletta et al, 2000 ; Gohda et al, 2001 ; D’Amico and Bazzi, 2003 ; Imai, 2003 ; Thorevska et al, 2003 ; Mäkelä et al, 2004 ; Wassmann et al, 2004 ; Kielar et al, 2005 ; Abbate et al, 2006 ; Liu et al, 2007 ; Delvaeye and Conway, 2009 ; Murugan et al, 2010 ; Ranganathan et al, 2013 ; Darmon et al, 2014 , 2017 ; Su et al, 2017 ; Sarhan et al, 2018 ; Meissner et al, 2019 ; Cremoni et al, 2020 ; Mehta et al, 2020 ; Pan et al, 2020 ; Rossi et al, 2020 ; Siddiqi and Mehra, 2020 ; Tang et al, 2020 ; Vaninov, 2020 ; Zhang et al, 2020 ; Ruetsch et al, 2021 ), release of pathogen-associated molecular patterns (PAMPs), high levels of damage-associated molecular proteins (DAMPS) from lung injury and severe hypoxemic respiratory failure ( Burton and Harris, 1996 ; Coletta et al, 2000 ; Gohda et al, 2001 ; D’Amico and Bazzi, 2003 ; Thorevska et al, 2003 ; Mäkelä et al, 2004 ; Wassmann et al, 2004 ; Kielar et al, 2005 ; Abbate et al, 2006 ; Delvaeye and Conway, 2009 ; Ranganathan et al, 2013 ; Darmon et al, 2014 , 2017 ; Su et al, 2017 ; Sarhan et al, 2018 ; Meissner et al, 2019 ; Cremoni et al, 2020 ; Pan et al, 2020 ; Rossi et al, 2020 ; Siddiqi and Mehra, 2020 ; Tang et al, 2020 ; Vaninov, 2020 ; Zhang et al, 2020 ; Ruetsch et a...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation of anti-PLA2R antibody induced renal injury and activation of coagulation deserves further investigation. On the other hand, a recent study demonstrated that MN patients with Th17-mediated in ammation had more VTEs [27]. Th17-immune response is a proin ammatory immune pathway associated with autoimmune diseases [28,29].…”
Section: Discussionmentioning
confidence: 98%